ANALYZING CELEBRITY IMPACT ON TIKTOK ON CAMILLE BEAUTY'S PURCHASE INTENTION - Julia Lathifah Kurniasari; Sentot Basuki Prayitno (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
In recent years, the rapid growth of social media platforms like TikTok has changed how beauty brands market their products, especially to younger audiences. This study, "Analyzing Celebrity Impact on TikTok on Camille Beauty's Purchase Intention,” looks at how celebrity endorsements on TikTok affect consumer behavior, focusing on Camille Beauty. The main goal is to see how Nadya Shavira's personal branding on TikTok impacts brand awareness, recall, and purchase intentions for Camille Beauty products. Data was collected from 100 respondents who follow Nadya Shavira on TikTok and engage with Camille Beauty's products. The findings show that Nadya Shavira's personal branding positively affects brand awareness and recall among her followers. Additionally, brand awareness and recall significantly boost the purchase intentions for Camille Beauty products. The study also finds that personal branding alone has a strong direct effect on consumers' purchase decisions, emphasizing the importance of influencer credibility and authenticity in the competitive beauty industry. These results show TikTok's effectiveness as a marketing tool for increasing brand awareness, recall, and purchase intentions through celebrity endorsements. Future research could build on these findings by looking at different social media platforms and a broader range of influencers to validate and generalize the results. Camille Beauty, a well-known local brand in Indonesia, is famous for its organic skincare products, especially its popular organic masks, which sell over 700,000 units per month. To higher purchase intentions. This underscores the importance of influencer credibility and authenticity in the beauty industry. The findings suggest TikTok is an effective platform for beauty brands to increase brand awareness, recall, and purchase intentions through celebrity endorsements. The research offers valuable insights for beauty brands and marketers to design better social media strategies by leveraging personal branding and influencer marketing. Future research could explore the impact of different social media platforms and a wider range of influences on consumer behavior, helping to validate and generalize the results across various contexts and industries, thus providing a clearer understanding of the role of social media in modern marketing strategies.